PENERAPAN STRATEGI SQ3R PADA KETERAMPILAN MEMBACA PEMAHAMAN PESERTA DIDIK KELAS IV UPT SD NEGERI 304 GRESIK - Rovita, Zulianah; Umam, Nanang Khoirul (Jurnal Al-Fatih, 2023)
This research is a qualitative descriptive study that aims to describe the implementation, responses of teacher and students and the difficulties exprerienced by students in implementing the SQ3R strategy (Survey, Question, Read, Recite, Review) during the learning process. “The subjects in this study were 25 students of grade IV UPT SD Negeri 304 Gresik. Data collection techniques used in this study were tests, interviews, observations. The results of this student indicate that activities are able to follow the SQ3R even thought the students had not previously learned about the SQ3R Strategy. Students can collect data independently and answer question made by themselves. The difficulties faced by students are asking questions and making conclusions from the contents of the reading text.